Detection of CTV in a citrus collection of Albania by immunoprinting - Stamo B.; D'Onghia A.M. (Proceedings of the Mediterranean network on certification of citrus. 1995-1997, 1998)
A survey was carried out using immonoprinting for the detection of citrus tristeza virus (CTV) in a varietal collection of the Institute of Pomology, Vlora. Seven out of 62 samples were CTV-infected. This is the first record of CTV in Albania.
Round Table on: Citrus Virus and Virus-like Diseases and Certification: State of the Art, 1995/07/21, Bari (Italy)